Breathomics for diagnosing tuberculosis in diabetes mellitus patients - Xu, Rong; Zhang, Ying; Li, Zhaodong; He, Mingjie; Lu, Hailin; Liu, Guizhen; Yang, Min; Fu, Liang; Chen, Xinchun; Deng, Guofang; Wang, Wenfei (Frontiers in Molecular Biosciences, 2024)
Introduction Individuals with diabetes mellitus (DM) are at an increased risk of Mycobacterium tuberculosis (Mtb) infection and progressing from latent tuberculosis (TB) infection to active tuberculosis disease. TB in the DM population is more likely to go undiagnosed due to smear-negative results. Methods Exhaled breath samples were collected and analyzed using high-pressure photon ionization time-of-flight mass spectrometry. An eXtreme Gradient Boosting (XGBoost) model was utilized for breathomics analysis and TB detection. Results XGBoost model achieved a sensitivity of 88.5%, specificity of 100%, accuracy of 90.2%, and an area under the curve (AUC) of 98.8%. The most significant feature across the entire set was m106, which demonstrated a sensitivity of 93%, specificity of 100%, and an AUC of 99.7%. Discussion The breathomics-based TB detection method utilizing m106 exhibited high sensitivity and specificity potentially beneficial for clinical TB screening and diagnosis in individuals with diabetes.